Identification and analysis of expression of human VACM-1, a cullin gene family member located on chromosome 11q22-23. - Byrd, P J; Stankovic, T; McConville, C M; Smith, A D; Cooper, P R; Taylor, A M (Genome Research, 1997)
We have localized the human homolog of the rabbit vasopressin-activated calcium-mobilizing receptor VACM-1 to a region close to the gene for ataxia telangiectasia ATM on chromosome 11q22-23. We have determined the complete amino acid sequence of the human Hs-VACM-1 protein, which is 780 amino acids long. The human and rabbit sequences are highly conserved, differing at only seven amino acids. Northern analysis of the human gene showed expression in a wide range of human tissues. The Hs-VACM-1 gene has homology with the Caenorhabditis elegans gene Ce-cul-5, a member of a family of cullin genes that are involved in cell cycle regulation and that might, when mutated, contribute to tumor progression.
10.1101/gr.7.1.71